1930-1943: Agrarian Transformation and the Famine in Bengal - Saumik Paul (Institute of Labor Economics (IZA), 2024)
Since the advent of British rule in 1765, the colony of Bengal, once hailed as the most fertile and prosperous region of India, witnessed numerous incidents of food shortages. Apart from the supply and demand side factors are typically associated with a food shortage at an escalated or disastrous level (famine), the role of persistent and long-term factors is also critical. This paper, both qualitatively and quantitatively, provides a deeper understanding of the process of agrarian transformation in Bengal. It argues that the 1943 Bengal famine could have been less likely had there been a buoyant agricultural credit market and a better patronage system with less exploitative farming practices. Quantitatively, I find that frequency of distress sale of occupancy holdings in the 1930s is positively associated with the famine intensity throughout many districts, and this relationship increases in the presence of sharecroppers' struggles.
Keywords: N; O; 330; famine; land transfer; Bengal